Distribution system dewatering in coal mining at PIT Sena Sungai Lilin District, Musi Banyuasin Regency, South Sumatra Province - Prabowo, Heri; Wahyudi, Wahyudi; Rolitu, Rolitu (Jurnal Pendidikan Teknologi Kejuruan, 2023)
The purpose of this research is to calculate the total design discharge of water entering the mining site in the sena pit of PT Putra Muba Coal (PMC), design the appropriate shape and dimensions of the sump to accommodate the amount of water entering the mining site and calculate the number of pumps needed to remove water entering the mine to the settling pond. The source of water entering the mine area comes from rainwater entering the mine opening, water runoff from the rainwater catchment area in the area around the mine opening, and groundwater rise. Based on the results of the analysis of rainfall data for 2013-2022, a rainfall plan of 77, 225 mm/day, rainfall intensity of 9.714 mm/hour with a rainfall return period of 2 years was obtained. The rainfall catchment area at the research site is 72,936 m2 with a discharge generated of 0.03 m3 / second and groundwater discharge of 0.00812 m3 / second. To remove the water entering the mine, it is flowed naturally into the sump with dimensions of 50 m length, 14 m top width, 13 m bottom width, and 5 m depth. The dimensions of the open channel are planned with a channel width of 32 cm, a flow depth of 28 cm, a wet cross-sectional area of 13.6 cm2, a wet circumference of 97 cm, a hydraulic radius of 9.25 cm, and a channel length of 233m. The water in the sump is pumped into an open channel. The pump used has a maximum discharge of 150 m3 / hour and a total pump head of 11.8712 m with a pipe diameter of 6 inches.